Addressing the HIV/AIDS investment gap through stronger public financial management systems: a human-centered approach - Carlyn Mann; Elan Reuben; Susanna Baker; Mai Hijazi; A. K. Nandakumar; Padma Shetty; Rob Stanley; Onyeka Igboelina; Godfrey Nyombi; Dhimn Nzoya; Samson Oli; Garoma Kena; et al. (BMC Health Services Research)
Abstract Background UNAIDS estimated that US$29 billion will be required by 2025 to meet HIV/AIDS service demands, with 53 percent expected to come from domestic sources. The PEPFAR-funded, USAID-implemented Sustainable Financing Initiative for HIV/AIDS (SFI), starting in 2014, supported domestic resources mobilization efforts and activities to strengthen countries' public financial management (PFM) systems, positively contributing to much-needed increase in domestic resources for health and HIV. Program approach SFI was implemented in 12 countries, supporting activities to build the capacity of governments to mobilize domestic resources for HIV, improve budget absorption, and maximize resource use and develop and use evidence for advocacy to increase domestic government funds for HIV/AIDS. SFI measured impact by agreed upon indicators and estimated return on investment (ROI). Results Eight countries focused on building capacity to improve budgeting and execution of health and HIV/AIDS funds; five experienced increases in budget allocation and spending. Kenya country governments spent an additional US$180 million and US$8.7 million on health and HIV, respectively. This contributed to US$60 mobilized and spent for every SFI dollar invested. Eight countries focused on using evidence to advocate for more domestic resources for health and HIV/AIDS from government budgets, increase budget execution, and identify areas for efficiency. Cambodia saw an increase in government commitments for ARVs from US$1.5 million annually from 2018–2020 to US$5 million by 2023. Lessons learned Robust data are needed for evidence-based advocacy to increase domestic government funding for HIV/AIDS and to strengthen PFM systems for more efficient and effective resource use; institutionalizing capacity building efforts allows for locally-led technical assistance; policy-related work is a multi-year endeavor; PFM success can be stymied by political transitions, political will, and donor commitments; COVID-19 brought new challenges and new opportunities; measurable results can lead to greater impact; and results are not necessarily solely project attributions with possible inflation of ROI estimates given there was no counterfactual. Conclusion Strengthening PFM systems can increase domestic resources for health and HIV through increased revenue and improved efficiency; closing the investment gap to end the HIV/AIDS epidemic by 2030.